Isolation and characterization of pink-pigmented, facultative methylotrophic (PPFM) bacteria from leaves of neem, Azadirachta indica A. Juss - Kumar, Rinki (Animo Repository, 2009)
A total of twenty isolates of pink-pigmented, facultative methylotrophic bacteria were obtained from the leaves of neem. All isolates exhibited pink to orange-pink pigmentation, entire margin, round colonies with a smooth glistening surface, and convex elevation. Most of the colonies were opaque with butyrous consistency. Staining revealed rod to coccobacilli shaped, Gram negative cells, containing poly-β-hydroxybutyrate granules. Biochemical analyses showed that all were catalase positive; majority of them were positive for citrate utilization, urease and oxidase activities but were negative for amylase activity. They can be cultivated on ammonium mineral salt (AMS) agar with methanol, glycerol peptone agar (GPA) and tryptic soy agar (TSA) with variations in colonial morphology. Based on the observed characteristics, the isolates obtained belong to the genus Methylobacterium.